PENGARUH ON THE JOB TRAINING DAN OFF THE JOB TRAINING TERHADAP KINERJA KARYAWAN (Studi Pada Karyawan Bagian Kantor PTPN V Unit Kebun Lubuk Dalam Kabupaten Siak) - Rahmi, Hidayatul; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study used 3 variables, namely: on the job training, off the job training, and employee performance. The on the job training had 2 dimensions, coaching and job rotatian. In the variable off the job training have 2 dimensions of simulation and presentation of information. In the variable Employee Performance has 3 dimensions of the quantity of work, quality of work, and timeliness. Objects in this study are employees of the Division at PTPN V Unit Kebun Lubuk In Siak Regency amounting to 77 employees. The analysis used in this research is Validity Test, Reliability Test, Simple Linear Regression, Multiple Linear Regression, Determination Test (R2), Individual for Significant Test (t test) and Significant Test (F test).The results showed the influence of On The Job Training and Off The Job Training on Employee Performance. The more frequent the On The Job Training and Off The Job Training then the better level of Employee Performance on the. Subsequently, the resulted data from quisoner is calculated and tested with statistics through SPSS program. The calculated result is known that R square is coefficient of determination. So that, it obtained the value of R square is about 0,511. It is meaned that the influence of variable On The Job Training and Off The Job Training variables was 51.1%. to employee perfomance variables.Keywords : On The Job Training, Off The Job Training, employee performance